A journey to the center of the earth - Verne, Jules, 1828-1905.; Schwach, Howard J.; Pablo Marcos Studio (Edina, Minn. : ABDO Pub., 2002)
Professor Hardwigg, his nephew Harry, and their guide Hans explore a volcanic crater in Iceland that leads them to the center of the Earth and to incredible and horrifying discoveries.
Originally published: New York : Playmore : Waldman Pub., 1990.
EL-Pro
Bichitra Library
Keywords: Explorers -- Fiction; Science fiction